Aqua-spiroergometry in a swimming flume to determine individual overall efficiency - Ungerechts, B. E.; Götz, J. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
This paper aims to present the calculation steps, taking into account the dimensional analysis and scaling as well as laws conservation of energy without speculating about the specific forces, which are difficult to determine separately. Moreover, data from an experiment on spiroergometry in the flume is used to answer a question asked by the swimmers. Swimmers asked how many watts they put out on their hands during one cycle? They had learned from cyclists that they were apparently well informed about how many watts they apply "on the padale".